The Influence of the Buillt Environment Quality of the Dukuh Atas TOD Pedestrian Area on Pedestrian’s Compfort Perception - Andri Candra Sambada; Deddy Wahjudi (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2025)
Jakarta faces a major challenge in creating sustainable urban mobility due to reliance on private vehicles that exacerbate congestion, air pollution, and degrade the quality of public spaces. The concept of Transit-Oriented Development (TOD) is present as a solution by prioritizing the development of areas around public transportation nodes to improve spatial efficiency and people's quality of life. This study focuses on the pedestrian area in Dukuh Atas, as part of the Jakarta TOD area, with the aim of identifying physical elements that affect walkability and comfort of pedestrian path users. The method used was exploratory sequential design, involving qualitative observation and distribution of questionnaires to 52 respondents of productive age (26–55 years). The findings show that physical elements such as trees and murals play a significant role in creating comfort and visual appeal, which are the main drivers of walkability. Regularly planted trees provide shade and a green ambiance, while the murals in the Kendal Tunnel enhance the aesthetics of the area through strong visual appeal. In addition, elements such as sidewalks, signage and street furniture also contribute to the user experience, although not as strong as green elements and murals. The results of this study support Rapoport and Speck's theory of the importance of fixed and semi-fixed physical elements in creating public spaces that are comfortable and attractive to pedestrians. With the integration of these elements, the TOD area has the potential to become a sustainable mobility solution, reduce dependence on private vehicles, and become a model for the development of inclusive and environmentally friendly public spaces for other major cities.